Frequency and Distribution of Parasites Detected in Children Between 2017-2022 (6-year Period) - Yelda Sorguç (Türkiye Parazitoloji Dergisi)
Objective: In the study, various complaints such as gastrointestinal complaints such as diarrhea, constipation, abdominal pain, nausea and vomiting, weight loss, night urination, itching around the anus, malnutrition, malabsorption, anemia, intelligence and developmental delay were reported to University of Health Sciences Türkiye, Dr. Behçet Uz Pediatric Diseases and Surgery Training and Researhc Hospital, Microbiology Laboratory between 2017 and 2022. It was aimed to determine the frequency and distribution of intestinal parasites in patients presenting with clinical symptoms. Methods: In the study, the results of 33,249 stool and 3499 cellophane tape samples sent to the microbiology laboratory between January 2017 and September 2022 were evaluated. The stool samples were examined with saline-Lugol, modified Kinyoun acid-fast and trichrome staining methods. Results: Parasites were detected in the stool samples of 1.8% of a total of 36,748 patients. The intestinal parasite detected at the highest rate was Entamoeba histolytica (67%). In order of frequency: Enterobius vermicularis (19%), Giardia intestinalis (12%), Ascaris lumbricoides (0.6%), Hymenolepis nana (0.2%) Blastocystis spp. (0.2%) is followed by Hymenolepis diminuta (0.2%). Conclusion: While the rate of parasite occurrence in patients applying was found to be 19.9% in 2017, 24.6% in 2018, and 28.6% in 2019, this rate decreased to 4.3% in 2020, 16% in 2021 and 6.6% in 2022. Looking at the distribution of parasites by years, it is seen that there was a decrease in the rate of parasite occurrence with the start of the Coronavirus disease-2019 pandemic in 2020. We believe that infection control measures and strict enforcement of quarantine rules to reduce the spread of severe acute respiratory syndrome-coronavirus-2 may have significantly reduced the parasite positivity rate during the pandemic period. Data on intestinal parasites in Türkiye show regional differences, and national surveillance studies are needed, especially in children.